A Metal–Organic Framework‐5‐Incorporated All‐Solid‐State Composite Polymer Electrolyte Membrane with Enhanced Performances for High‐Safety Lithium‐Ion Batteries. Issue 2 (10th December 2020) - Wen, Wen; Wang, Zhinan; Wang, Ailian; Zeng, Qinghui; Chen, Pingping; Wen, Xin; Li, Zhenfeng; Li, Zengxi; Liu, Wei; Zhang, Liaoyun
Abstract : Solid polymer electrolytes (SPEs) have been one of the most promising candidates to replace nonaqueous liquid electrolyte for achieving high‐safety lithium‐ion batteries (LIBs). However, the extremely low ionic transport capacities of SPEs have seriously hindered their applications in LIBs. Herein, a metal–organic framework (MOF) material MOF‐5 is applied to polymer electrolyte for enhancing electrochemical performances of SPEs. Specifically, a polymer matrix is first obtained via a strategy of random copolymerization of trifluoroethyl methacrylate (TFEMA) and poly(ethylene glycol) methacrylate (PEGMA). Then, a free‐standing flexible composite SPE (CSPE) membrane composed of P(TFEMA‐ ran ‐PEGMA) polymer, lithium salt, and MOF‐5 (nanofillers) is prepared by the solution casting technique. The results indicate that the room temperature ionic conductivity of the CSPE is 1.5 times higher than that of neat SPEs and lithium‐ion transference number of CSPE remarkably enhances from 0.25 to 0.51. In addition, the as‐prepared CSPE has a very wide electrochemical window of 5.38 V. Moreover, the assembled solid cell LiFePO4 /CSPE/Li presents an outstanding specific discharge capacity retention of 92.2% after 25 cycles. Thus, the superior comprehensive properties of the MOF‐incorporated composite polymer electrolyte exhibit a promising potential application in solid electrolyte for high‐safety solid LIBs. Abstract : Herein, a metal–organic framework‐5 (MOF‐5)‐incorporated composite solid polymer electrolyte for all‐solid‐state Li‐metal batteries is prepared. The fluorinated polymer (PTFEMA‐ co ‐PPEGMA) matrix provides good film‐forming properties. Furthermore, the MOF‐5 nanoparticles play an important role in the enhancement of electrochemical performance. A high t Li + (0.51) and a wide electrochemical window (5.38 V) are achieved after the incorporation of MOF‐5 fillers into matrix.